Conflict regulation of adoption and tutelage (guardianship) of minors: comparative law aspects - Miashchanava, Maryia V. (Journal of the Belarusian State University. Law, 2019)
This article looks at the peculiarities of conflict regulation of adoption and tutelage (guardianship) under the legislation of the Eurasian Economic Union and European Union. The conclusion is that, the absence of corresponding provisions in the family legislation of the Republic of Belarus does not meet the modern needs of the regulation of relations with a foreign element. Suggestions are made about the most progressive conflict rules that can be incorporated into the national legal order.